Police Functional Adaptation to the Digital or Post Digital Age: Discussions with Cybercrime Experts. (October 2020) - Johnson, Derek; Faulkner, Erin; Meredith, Georgia; Wilson, Tim J
This article examines the challenges of functional adaptation faced by the police in response to technologically driven changes in the nature of crime. It also recounts how research under the auspices of a 'dark web' research project resulted in a search for an effective approach to engaging with investigators dealing with cybercrime. In doing so it tested, as a research methodology, a standard change implementation tool (problem tree analysis) from the Disaster Management and Sustainable Development (DMSD) discipline. This in turn resulted in significant consideration being given to the physical space in which that methodology is used. It presents the results of a workshop held with cybercrime investigators (not all were police officers) in terms of the importance of four key organisational and cultural issues (management, leadership and institutional ethos within the police; the risks of over-complication and exaggerated distinctions between cyber and real world policing; ethics; and knowledge, training and development) alongside the development and acquisition of new technical capabilities.